Effectiveness of Criminal Offense Law Regarding Illegal Levies: Reforming Social Organizations within the Indonesian Legal Framework - Muhammad Ishar Helmi; Pujiyono Pujiyono; Khamami Zada; Mara Sutan Rambe; Mualimin Mochammad Sahid (Faculty of Sharia Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
Non-Indexed Publication